Predictors of Prolonged Length of Stay After Lumbar Interbody Fusion: A Multicenter Study. Issue 5 (August 2019) - Kobayashi, Kazuyoshi; Ando, Kei; Kato, Fumihiko; Kanemura, Tokumi; Sato, Koji; Hachiya, Yudo; Matsubara, Yuji; Kamiya, Mitsuhiro; Sakai, Yoshihito; Yagi, Hideki; Shinjo, Ryuichi; Ishiguro, Naoki; et al.
Study Design: Retrospective analysis of a prospectively database. Objectives: To identify factors associated with prolonged length of stay (LOS) in posterior /transforaminal lumbar interbody fusion (PLIF/TLIF). Methods: The subjects were patients who underwent PLIF/TLIF at 10 facilities from 2012 to 2014. A total of 1168 such patients with a mean age of 65.9 ± 12.5 years (range 18-87 years) were identified in the database. Operations were PLIF (n = 675), TLIF (n = 443), minimally invasive surgery (MIS)-PLIF (n = 22), and MIS-TLIF (n = 32). Age, gender, body mass index, ambulatory status, comorbidities, perioperative American Society of Anesthesiologists (ASA) grade, operative factors, and complications were examined. LOS was defined as the number of calendar days from the operation to hospital discharge. LOS was categorized as normal (<75th percentile) or prolonged (≥75th percentile). Results: The average LOS was 20.8 ± 9.8 days (range 7-77 days). There was a significant correlation between LOS and age ( P < .05). Reoperation during hospitalization was performed in 20 cases for surgical site infection (n = 12), epidural hematoma (n = 5), and screw misplacement (n = 3). In multivariate analysis, prolonged LOS was associated with preoperative variables of age ≥70 years (odds ratio [OR] 1.87, 95% CI 1.38-2.54), and ASA class ≥III (OR 1.52, 95% CI 1.04-2.25); surgical variables of open procedures (OR 5.84, 95% CI 1.74-19.63), fused levels ≥3 (OR 5.17, 95% CI 3.17-8.43), operative time ≥300 minutes (OR 1.88, 95% CI 1.15-3.07), and estimated blood loss ≥500 mL (OR 1.71, 95% 1.07-2.75). Conclusions: The factors identified in this study should help with obtaining informed consent, surgical planning and complication prevention to reduce health care costs associated with prolonged LOS.